Optimization of Container Bonding Process to Improve Safety of Work and Cargo: Case Analysis at KM. Hijau Sejuk - Hidayat, Zulhikam Komaril; Kuncowati, Kuncowati; Wiyono, Teguh (Universitas Hang Tuah, 2025)
Research with the title “Optimalization of Container Tightening Processes to Increase Work Safety and Their Souls: Case Analysis at KM. Hijau Sejuk”. Optimization of bonding is vital because it is the most important part of the safety of mutant goods and ships. This study aims to find out what are the obstacles faced when optimizing container lashing and how to optimize safe container lashing to improve work safety and cargo on KM. Hijau Sejuk. This research uses a qualitative descriptive method by using 3 data collection techniques including data from the prala place, namely the KM. Hijau Sejuk. The theoretical basis used is the theory that includes lashing tools and how to use them correctly according to the applicable SOP. The conclusion that the binding of containers on KM. Hijau Sejuk is less efficient such as, there is damage to the lashing tool, so that it can cause the lack of safety that occurs in the cargo.